Harnessing Biomass for Sustainable Insect Farming and Biotechnology: Ecological Roles, Industrial Applications, and Future Opportunities - Pragya Yadav; A.K Sharma (International Journal of Insects, 2025)
Biomass, derived from biological materials, such as plant residues, animal waste, and agricultural by-products, plays a pivotal role in ecological systems, including those involving insects. Insects interact with biomass at multiple levels, serving as decomposers, pollinators, and converters of organic matter into valuable resources. The integration of biomass into insect ecology and farming has garnered significant attention for its potential in sustainable agriculture, waste management, and biotechnology. This review highlights the importance of biomass in insect farming, particularly its role as a feedstock for mass-rearing economically significant species, such as black soldier flies (Hermetia illucens) and mealworms (Tenebrio molitor). These insects efficiently convert agricultural residues, food waste, and other biomass into high-protein feed for animals and biofertilizers, contributing to circular economy models. Furthermore, the decomposition of biomass by insects enhances soil quality and nutrient cycling, underscoring their ecological importance. Biomass also serves as a resource for insects in natural ecosystems. For instance, termites and wood-boring beetles break down woody biomass, facilitating the recycling of carbon and nutrients. Pollinators rely on biomass-derived nectar and pollen plants, crucial for maintaining biodiversity and agricultural productivity. The potential of insect-driven biomass conversion is not limited to ecological services but extends to industrial applications. Emerging technologies are leveraging insects to produce biofuels and biopolymers, offering innovative solutions to global energy and material demands. Despite these advancements, challenges persist, including optimizing biomass processing for insect consumption, managing environmental impacts, and addressing scalability concerns in industrial applications. The review identifies opportunities for integrating biomass management with insect farming to enhance sustainability across food, energy, and agricultural sectors. Biomass is a critical resource in insect-related applications, spanning ecology, farming, and biotechnology. By harnessing the synergistic relationship between insects and biomass, we can address pressing environmental and economic challenges, fostering a more sustainable future. This review provides insights into the current practices, benefits, and future directions of biomass utilization in insect systems, encouraging interdisciplinary research and innovation in this field.
Keywords: biomass; biotechnology environmental; fertilizers; insects